(untitled) - Jefta Harlianto (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
In a competitive globalized world, human resource holds important roles to move the company. To be able to compete with other companies, employees need to have better competency. Competency consists of knowledge, skill, and attitude. These three aspects determine behaviors that will support the employee performance in a company. XYZ Foundation is a foundation that pays big attention to their employee competency development because XYZ Foundation realizes how important employee competency is to achieve vision and mission of the organization. XYZ Foundation wants to know if there is a correlation between competencies that have been set to the employee performance improvement. Researcher collects Core Competency and Key Performance Indicator score from 1075 of XYZ Foundation employees. Based on correlation analysis using Pearson Correlation and Test of Significance, researcher concluded that there is strong correlation (0.959) and significance (0.000) between employee Core Competency and Key Performance Indicator score In addition, there is strong correlation between each component in Core Competency to Key Performance Indicator of the employees: Business Acumen (0.952), Innovation (0.951), Operation Excellence (0.954), Personal Development (0.953), Service Excellence (0.951), with significance of 0.000 for each component, and there are strong correlation and significance between each component in Code Competency with the Core Competency score in XYZ Foundation Employee: Business Acumen (0.993), Innovation (0.991), Operation Excellence (0.993), Personal Development (0.994), Service Excellence (0.993), with level of significance 0.000 for each component.